Development of spacer warp knitted thermoelectric generators. (18th February 2021) - Dallmann, Anke; Franz, Christian; Hoffmann, Gerald; Cherif, Chokri
Abstract: The research presented in this paper was aimed at developing spacer warp knitted thermoelectric generators (TEGs), which can generate electrical current from waste heat. Hence, this paper introduces a structural design approach and a calculation model in addition to describing the manufacturing of prototypes and analyses on their basic functionality regarding thermoelectric power generation. Wires as well as wire strands of iron and constantan can be used for knitting on a double bar raschel machine. Wires can be connected to a thermocouple (TC) by means of various spacer warp knitting patterns while using the feed system of the spacer yarn for the wires. The friction locking electrical contacting of several TC, thus forming an applicable TEG, was achieved by sewing together silver plated copper wire strands. A large wire cross section, clear separation of iron and con-stantan wires in the knitted fabric, and consistently high temperature difference between the TEG surfaces produce a constant thermoelectric voltage. The maximum voltage depends on the number of TC, the material properties, and the temperature difference. By reducing the internal resistance of the TEG, electric power can be increased.